Travels, Explorations and Empires, 1770-1835, Part II Vol 8 : Travel Writings on North America, the Far East, North and South Poles and the Middle East /: Travel Writings on North America, the Far East, North and South Poles and the Middle East. (2021) - Fulford, Tim; Kitson, Peter; Youngs, Tim
No abstract available